Effects of Impella on Coronary Perfusion in Patients With Critical Coronary Artery Stenosis. (April 2018) - Alqarqaz, Mohammad; Basir, Mir; Alaswad, Khaldoon; O'Neill, William
Abstract : Background—: Mechanical circulatory support devices are used to maintain hemodynamic stability during high-risk percutaneous coronary interventions. Little is known on the effects of such devices on coronary hemodynamics in patients with significant coronary stenosis. We sought to investigate whether mechanical circulatory support in the form of Impella (Abiomed Inc, Danvers, MA) can improve coronary hemodynamics in the presence of a critical coronary stenosis. Methods and Results—: We examined coronary perfusion pressures and coronary pressure distal to a critical stenosis using a coronary pressure wire in 11 patients (12 coronary lesions) undergoing high-risk percutaneous coronary interventions with the use of mechanical circulatory support. Systemic, ventricular, and coronary hemodynamics were obtained at both minimum and maximum support levels before high-risk percutaneous coronary interventions. All patients had obstructive lesions with angiographically estimated diameter stenosis between 70% and 99% and distal coronary artery pressure to aortic pressure ratios between 0.44 and 0.88. When compared with minimum support, maximum support resulted in a decrease in the left ventricular end-diastolic pressure (27.3±8.6 versus 21.5±5.2 mm Hg; P =0.002) and increases in the mean systemic blood pressure (77.6±13.5 versus 88.2±12.2 mm Hg; P <0.001) and mean distal coronary pressure (51.8±20.2 versus 60.8±18.1 mm Hg; P <0.001). Effective coronary perfusion pressure (mean aortic pressure–left ventricular end-diastolic pressure) significantly increased with maximum support (49.8±15.7 versus 67.2±13.6 mm Hg; P <0.001). Diastolic perfusion pressure (diastolic blood pressure–left ventricular end-diastolic pressure) also significantly increased with maximum support (32.9±13.4 versus 52.0±11.6 mm Hg; P <0.001). Conclusions—: Mechanical circulatory support with Impella can improve distal coronary pressure and coronary perfusion pressures in the presence of critical coronary stenosis.